Simulation Study of Strains Obtained by Two Different Scattering Processes in Optical Fiber Sensors - Chakrabarti, Kisalaya; Shiwa, Mitsuharu (International Journal of Computer Sciences and Engineering, 2025)
Distributed Sensing plays a key role in the realm of modern sensing technology and fiber optic sensors are the ultimate choice for that. Fiber optic distributed sensors are extremely popular because it can able to measure strain and temperature difference with very high resolution of about 2 cm. In this paper we have tried to simulate the process of measuring the strains using Stimulated Brillouin and Rayleigh scattering by FDTD method and tried to investigate how well it will match with the strains obtained from the experimental process. These distributed sensors are used to monitor mainly the structural health of the civil or mechanical engineering systems and are facilitate to develop advanced sensing devices like Distributed Acoustic Sensors.